Pilot implementation of community health advocacy teams to improve the effectiveness of long-lasting insecticide net distribution through both campaigns and continuous channels in Ghana: a qualitative study of opportunities and barriers to implementation - Dako-Gyeke, Phyllis; Hornuvo, Ruby; Glozah, Franklin N.; Asampong, Emmanuel; Tabong, Philip Teg-Nefaah; Nwameme, Adanna; Chandi, Gloria. M.; Peprah, Nana Yaw; Gittelman, David; Adongo, Philip B. (Frontiers in Public Health, 2023)
The National Malaria Elimination Programme (NMEP) of Ghana distributes Long-Lasting Insecticide Net (LLIN) to households for free through the periodic Point Mass Distribution (PMD) campaign and continuous distribution to populations most vulnerable to malaria. It is known that the existence of effective and functional community-based groups could influence positive behaviours regarding health interventions promoted through health campaigns. However, there is no evidence of functional community-based groups that aim to improve the effectiveness of LLIN Distribution Campaigns through transitioning into primary healthcare delivery. This study aims to explore the opportunities and barriers to the pilot implementation of co-created community health advocacy teams (CHAT) to improve the effectiveness of LLIN distribution through both campaigns and continuous channels in Ghana.A qualitative research approach was used among 43 CHAT members across six communities in the Eastern and Volta regions of Ghana. The CHAT constitutes significant community actors whose Pilot Implementation of Community Health Advocacy Teams roles are centred on key elements of community/social mobilization and capacity building, all nested in social and behaviour change communication strategies. The CHATs were pilot implemented in all study communities for four months after which we identified opportunities and barriers during implementation. CHAT members participated in six Focus Group Discussions which were audio recorded, transcribed verbatim, and analyzed thematically using the NVivo 13.Results: CHATs were instrumental in sensitizing community members through social and behaviour change communication strategies. Also, there were changes in the behaviour of community members who were receptive towards, and participated in CHAT activities. Community members were accurately informed about malaria (e.g., causes, preventive measures). However, the CHAT experienced barriers during implementation, including lack of financial support to aid in transportation, organization of meetings, and outreach activities. Additionally, level of participation by CHAT members in activities, as well as medium of communication among members were key areas of concern.The CHATs would be instrumental in promoting LLINs use during and after PMD campaigns through community outreaches. It is therefore necessary to provide resources to support their operations and good network to address communication barriers. Finally, continuous capacity strengthening of CHAT members by the NMCP is important.